Cocreation of a digital patient health hub to enhance education and person-centred integrated care post hip fracture: a mixed-methods study protocol - Renuka Visvanathan; Tiffany K Gill; Lalit Yadav; Anita Taylor; Unyime Jasper; Jen De Young; Mellick J Chehade (BMJ Open)
Introduction Older people with hip fractures often require long-term care and a crucial aspect is the provision of quality health information to patients and their carers to support continuity of care. If patients are well informed about their health condition and caring needs, particularly posthospital discharge into the community setting, this may support recovery and improve quality of life. As internet and mobile access reach every household, it is possible to deliver a new model of service using a digital education platform as a personal health hub where both patients and their providers of care can establish a more efficient information integration and exchange process. This protocol details proposed research, which aims to develop a ‘model of care’ by using a digital health solution that will allow delivery of high quality and patient-centred information, integrated into the existing process delivered within the community setting.Methods and analysis This phase of the study uses a pragmatic mixed-methods design and a participatory approach through engagement of patients, their carers and healthcare providers from multiple disciplines to inform the development of a digital health platform. Quantitative methods will explore health literacy and e-health literacy among older people with hip fractures admitted to the two public tertiary care hospitals in Adelaide, South Australia. Qualitative methods will provide an understanding of aspects of content and context required for the digital health platform to be developed in order to deliver quality health information. The study will use appropriate theoretical frameworks and constructs to guide the design, analysis and overall conduct of the research study. The scope of the study intends to ultimately empower patients and their carers to improve self-management and to better use coordinated services at the community level. This could prevent further falls including associated injuries or new fractures; reduce new hospital admissions and improve confidence and engagement by limiting the psychologically restrictive ‘fear of falls’.Ethics and dissemination The study has been approved by the Human Research Ethics Committee of the Central Adelaide Local Health Network, South Australia (SA) Health, Government of South Australia and the University of Adelaide Human Research Ethics Committee. Findings from the study will be published in suitable peer-reviewed journals and disseminated through workshops or conferences.